Oxidative Stress and Complement Activation in Aqueous Cells and Vitreous from Patient with Vitreoretinal Diseases: Comparison Between Diabetic ERM and PDR - Lucia Dinice; Pamela Cosimi; Graziana Esposito; Fabio Scarinci; Andrea Cacciamani; Concetta Cafiero; Luca Placentino; Guido Ripandelli; Alessandra Micera (Antioxidants)
Background: Epiretinal membrane (ERM) and proliferative diabetic retinopathy (PDR) belong to the group of vitreoretinal diseases, characterized by impairments at both the retina and the vitreous. The non-diabetic and diabetic forms of ERM (no-dERM and dERM) as well as the PDR are caused by microvascular disorder, which frequently occurs in association with inflammation and oxidative stress. To better characterize no-dERM, dERM, and PDR at the biomolecular level, we compared the expression of inflammatory, oxidative, lipidic peroxidation products, and complement receptors. Methods: Twenty-seven ocular fluids from patients who underwent phaco-vitrectomy were categorized as no-dERM (9, 4M/5F; 70.4 ± 6.4), dERM (6, 3M/3F; 73.2 ± 4.9), and PDR (6, 5M/1F; 63.7 ± 7.4). Six cataracts (CTR; 3M/3F; 77.7 ± 9.0) were collected for internal control of aqueous cells. Results: In aqueous cells, p65NFkB, iNOS, Nox1/Nox4, and Nrf2 were significantly upregulated, and Keap1 was downregulated in dERM compared with PDR and no-dERM. In aqueous cells, a significant upregulation for C3aR1mRNA, C5aR1mRNA, and CFHmRNA were observed in dERM. In vitreous, C3a, C5b9, and MDA levels were significantly increased in dERM compared with PDR and no-dERM. Conclusions: Inflammatory and ROS products, as well as C3aR1/C5aR1 and soluble MDA, appear of great interest, as their expression in aqueous and vitreous might have potential prognostic and therapeutic values.